2016
DOI: 10.1111/1471-0528.14020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ovarian stimulation on the outcome of intrauterine insemination treatment: an analysis of 8893 cycles

Abstract: Objective To evaluate the impact of ovarian stimulation on the outcome of intrauterine insemination (IUI). Design Retrospective analysis. Setting A single university‐based centre. Population A total of 5109 couples with 8893 cycles. Methods The outcome of IUI with different protocols for ovarian stimulation was examined. Main outcome measures The live birth rate (LBR), twin pregnancy rate and ovarian hyperstimulation syndrome (OHSS). Results In ovulatory women without ovarian stimulation, the LBR was 7.6%. Sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In addition, Liu et al [ 12 ] concluded that ovarian stimulation in ovulatory women undergoing IUI appeared to have a limited role, with the exception of LE and HMG. In their study, when all ovarian stimulation protocols were combined, no differences in pregnancy or live birth rates were found in ovulatory women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Liu et al [ 12 ] concluded that ovarian stimulation in ovulatory women undergoing IUI appeared to have a limited role, with the exception of LE and HMG. In their study, when all ovarian stimulation protocols were combined, no differences in pregnancy or live birth rates were found in ovulatory women.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the HHU and LIN studies, types of ovarian stimulation were distributed equally between the IUI and SRI groups (Table 2 ), whereas Muharib et al had not used ovarian stimulation at all [ 10 ]. Although ovarian stimulation is well known to improve IUI outcome [ 2 , 21 ], its lack in some cases should not have influenced the main results of this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, when IUI is used, should ovarian stimulation be used at the same time? Some investigators have advocated using the natural cycle whereas others have claimed that ovarian stimulation may lead to better results [3].…”
Section: Introductionmentioning
confidence: 99%